Strategi Pemerintah Desa Pune dalam Pengembangan Pariwisata Tanjung Bongo Halmahera Utara - Itje, Deki; Kanaha, Ibnu (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study is to determine the policy strategy of the Pune Village Government in developing tourism. Data collection methods, participatory observation, in-depth interviews, and documentation. Research instruments, Village Head Tourism Manager, Community as Local Tourism Objects in Pune Village, Galela District, North Halmahera Regency. The results of the study found that, to develop tourism objects, the Pune Village government needs to use analysis of Tourism Development indicators that. (1) The Village Government provides facilities available at the Tanjung Bongo tourist attraction, namely a resting place or gazebo. (2) The government works with the community to create a resting place for tourists who visit to rest. (3) Promotion or marketing of the Tanjong Bongo tourist attraction is carried out through social media and advertisements in the form of banners and billboards. (4) The availability of communication or signal in the tourist area is not very supportive. However, there are several cellular networks that can be used at certain locations. This division is carried out to provide benefits to residents because they can obtain results from the UMKM community in the tourist area. The impact caused by the Tanjung Bongo tourist attraction is very good in the community empowerment sector. In addition, the condition or condition is good in terms of the sea has a very good hol and sea air for tourists to rest. The strategy of the Village government is expected to be able to develop the tourism potential that is owned both in terms of products and services, so that it can attract tourists both local and foreign which in the end can increase the Regional Original Income (PAD) and Village Original Income (PADes) through tax revenue from each tourist destination, Tanjung Bongo tourist attraction owned by the area.